Sol-gel Er-doped SiO(2)-HfO(2) planar waveguides: A viable system for 1.5 mu m application - Goncalves, R. R.; Carturan, G.; Zampedri, L.; Ferrari, M.; Montagna, M.; Chiasera, A.; Righini, G. C.; Pelli, S.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2002)
70SiO(2)-30HfO(2) planar waveguides, doped with Er(3+) concentrations ranging from 0.3 to 1 mol %, were prepared by sol-gel route, using dip-coating deposition on silica glass substrates. The waveguides show high densification degree, effective intermingling of the two components of the film, and uniform surface morphology. Propagation losses of about 1 dB/cm were measured at 632.8 nm. When pumped with 987 or 514.5 nm continuous-wave laser light, the waveguides show the (4)I(13/2)-->(4)I(15/2) emission band with a bandwidth of 48 nm. The spectral features are found independent both on erbium content and excitation wavelength. The (4)I(13/2) level decay curves presented a single-exponential profile, with a lifetime between 2.9 and 5.0 ms, depending on the erbium concentration. (C) 2002 American Institute of Physics.